Characterization of infectious salmon anaemia virus survival and infectivity in seawater - Simon Chioma Weli; Marit Måsøy Amundsen; Ole Bendik Dale; Sonal Jayesh Patel (Aquaculture Reports)
Infectious salmon anaemia virus (ISAV) is a water-borne virus that cause infectious salmon anaemia in Atlantic salmon. Virulent ISAV primarily infects salmon and replicates within salmon, which then shed virus particles potentially infecting naïve salmon. However, spread of this pathogen from net-pen to net-pen is often remarkably slow as it may take months despite net-pens being only a few meters apart. The time period for ISAV survival and persistence in seawater under various environmental conditions is debated. We designed in vitro experiments to study infectivity of two Norwegian ISAV isolates, in natural non-sterile seawater (NSW). One of the ISAV isolates originates from 1990s (ISAV-Glesvær; ISAV-G), while the second was isolated in 2022 (ISAV-Hønsvikgulen; ISAV-H), representing recent outbreak. Using RT-qPCR we were able to detect the 1990s isolate for up to five days and the 2022 isolate for up to eight days in NSW. The pattern of survival and infectivity, as analyzed by RT-qPCR and cell culture assays, combined with indirect immunofluorescence antibody test (IFAT) were largely similar and repeatable. In addition, the intensity of positive IFAT staining of cells infected with the eluted spiked seawater was proportional to the viral load obtained by RT-qPCR. However, while viral RNA could be detected at high amounts in samples from day five and day eight respectively for ISAV-G and ISAV-H incubated at 15 ℃, we could not demonstrate infective particles from these samples. Survival was dependent on temperature and on initial concentrations, and our findings indicate that low initial numbers of virus particles combined with high incubation temperature reduces survival and infectivity. The data in this study are relevant for decision making regarding various ISA control measures such as cull, disinfection and fallowing, following ISAV infection and disease outbreak.